Strategies of transformation of libraries informational technological basis - Tavalbekh A. (Kharkov National Pedagogical University, 2010)
Questions of evolution of informational technologies in library sphere are considered. They are providing necessary level of satisfaction of society needs in information and knowledge. Substantial sights of technological progression are becoming changes of ways of influence on information in any form and its complex unification. Development staging of technological basis of library from learning of computer, information communicational technologies to multimedia technologies is observing. Vector of changes of library strategies of library basis development is determined.